El o los fines de la etnografía: del desorden de lo experimental al desorden de lo barroco - Marcus, George E. (Revista de Antropología Social, 2008)
Since the 1980s, and the Writing Culture critique of ethnographic representation, the writing of ethnographic texts in anthropology has been distinguished by the perennial appearance by neophytes of new works composed of tropes and stylistic strategies that reflect the diverse influences of the period of critique. These “messy” texts were, and are, valorizied as experiments. This essay argues as critique that current such ethnographies are not so much experimental as baroque. Indicating perhaps a limit of the historic ethnographic form, and the need to push the spirit of experiment back toward the conditions of producing ethnography in fieldwork. This “refunctioning” of ethnography in its experimental spirit would recognize and address the present limit of the baroque to which the 1980s period of critique and after has led.